Developing Research in Infectious and Tropical Diseases in Africa: The Paradigm of Senegal - (:unkn) unknown (My University, 2017)
Infectious diseases represent one of the greatest potential barriers to achievement of the third Sustainable Development Goals in African countries and around the world because they continue to pose major public health challenges. The surveillance of infectious diseases has recently assumed greater importance in most African countries, both because of the emergence of infectious diseases and because strains of pathogens that cause tuberculosis, malaria, cholera, dysentery, and pneumonia have developed resistance to common and inexpensive antimicrobial drugs. However, data on the pathogen-specific causes of infectious diseases are limited. Developing research in infectious and tropical diseases in Africa is urgently needed to better describe the distribution of pathogen-borne diseases and to know which pathogens actually cause fever. This research is critical for guiding treatment and policies in Africa. More effective diagnostics are also needed for these diseases, which often are misdiagnosed or diagnosed too late. A comprehensive review of this type of research is presented here.
Keywords: African Research